Natural infection with Leishmania (Mundinia) martiniquensis supports Culicoides peregrinus (Diptera: Ceratopogonidae) as a potential vector of leishmaniasis and characterization of a Crithidia sp. isolated from the midges - Kaewmee, Saowalak; Mano, Chonlada; Phanitchakun, Thanari; Ampol, Rinnara; Yasanga, Thippawan; Pattanawong, Urassaya; Junkum, Anuluck; Siriyasatien, Padet; Bates, Paul A.; Jariyapan, Narissara (Frontiers in Microbiology, 2023)
The prevalence of autochthonous leishmaniasis in Thailand is increasing but the natural vectors that are responsible for transmission remain unknown. Experimental in vivo infections in Culicoides spp. with Leishmania (Mundinia) martiniquensis and Leishmania (Mundinia) orientalis, the major causative pathogens in Thailand, have demonstrated that biting midges can act as competent vectors. Therefore, the isolation and detection of Leishmania and other trypanosomatids were performed in biting midges collected at a field site in an endemic area of leishmaniasis in Tha Ruea and a mixed farm of chickens, goats, and cattle in Khuan Phang, Nakhon Si Thammarat province, southern Thailand. Results showed that Culicoides peregrinus was the abundant species (> 84%) found in both locations and only cow blood DNA was detected in engorged females. Microscopic examination revealed various forms of Leishmania promastigotes in the foregut of several C. peregrinus in the absence of bloodmeal remnants, indicating established infections. Molecular identification using ITS1 and 3’UTR HSP70 type I markers showed that the Leishmania parasites found in the midges were L. martiniquensis. The infection rate of L. martiniquensis in the collected flies was 2% in Tha Ruea and 6% in Khuan Phang, but no L. orientalis DNA or parasites were found. Additionally, organisms from two different clades of Crithidia, both possibly new species, were identified using SSU rRNA and gGAPDH genes. Choanomastigotes and promastigotes of both Crithidia spp. were observed in the hindgut of the dissected C. peregrinus. Interestingly, midges infected with both L. martiniquensis and Crithidia were found. Moreover, four strains of Crithidia from one of the clades were successfully isolated into culture. These parasites could grow at 37 ºC in the culture and infect BALB/c mice macrophages but no multiplication was observed, suggesting they are thermotolerant monoxenous trypanosomatids similar to Cr. thermophila. These findings provide the first evidence of natural infection of L. martiniquensis in C. peregrinus supporting it as a potential vector of L. martiniquensis.